Proposed Marketing Strategy for Inspirator Freak - Christian Susanto, Jonathan; Kartajaya, Hermawan (The Indonesian Journal of Business Administration, 2019)
Abstract – PT. Berkat Inspirasi Indonesia, also known as InspiratorFreak.com is a digital media company for millennials in Indonesia. However the problem arise when their traffic is not increase significantly or stagnan. This caused low of positioning and value proposition of their product, so the content is not related with their target audience. Morover InspiratorFreak get support from voluntary team, which is not a full time employee and they don’t have digital marketing staff to increase their productivity and their traffic in website and social media. The approach of this resarch is to analyze secondary data which is the internal and external factor which set by the company for the marketing division, and to compare with the web traffic of InspiratorFreak in 2018. External factor analysis was conducted using PESTEL Analysis, Porter’s Five Forces, and Competitor Analysis with 4Ps. Internal factor analysis conducted using Business Model Analysis, Value Proposition Analysis, STP Analysis and Marketing Mix Analysis. From that analysis, it has been founded that InspiratorFreak  has strength in reputation and networking but weakness in positioning and value proposition. InspiratorFreak still has a big opportunity to improve their business due to increase of internet users in Indonesia. However, threats from external factor still need to be aware. Research result show that InspiratorFreak need to improve their segmentation, targeting and especially their positioning and value proposition. The recommended strategic plan for InspiratorFreak in digital marketing strategy with E-Integrated Marketing Communication (E-IMC) approach and also Content Marketing Strategy to increase their quality of their content. Keywords: Marketing, Digital Marketing, Digital Media, Millennials, StartupABSTRAK